The Brazilian Amazonian species of Hymenoepimecis Viereck, 1912 (Hymenoptera: Ichneumonidae: Pimplinae) - Pádua, Diego G.; Oliveira, Marcio L.; Onody, Helena C.; Sobczak, Jober F.; Sääksjärvi, Ilari E.; Gómez, Isrrael C. (Zootaxa, 2015)
Six new species of Hymenoepimecis Viereck are described from Brazilian Amazonian tropical forest: H. amazonensis sp. n., H. duckensis sp. n., H. kleini sp. n., H. manauara sp. n., H. ribeiroi sp. n. and H. uberensis sp. n., and male genitalia is described for the first time for the genus. In addition, we provide an identification key, diagnosis and distributional records for Brazilian Amazonian species of Hymenoepimecis. By describing these new species we aim to draw further attention to the considerable species richness of the genus in Amazonia.